Minutes of the 42nd Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of Minutes of the 41st Meeting of the Academic Council. 2. Review of the progress and implementation of decisions of the 41st Meeting of the Academic Council. 3. Proposal for Major in Media, Cultural Studies and Journalism. 4. Proposal for Minor in History. 5. Approval of the Academic Calendar of Pharmacy (Year 2011-12). 6. Approval of the New Academic Calendar of year 2012. 7. Proposal for Hospitality and Tourism Management. 8. Review of BRACU Marking System. 9. Continuation of Studies beyond 3rd times probations. 10. Proposal for M.A. in Teaching English to Speakers of Other Languages. 11. Proposal for BRAC Institute of Languages (BlL).